Effects of bentazon and paraquat mixtures on weeds and on dry beans (Phaseolus vulgaris L.) - Rodrigues, B.N.; Victoria Filho, R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1983)
The present research was conducted at Escola Superior de Agricultura "Luiz de Queiroz", Piracicaba, SP, in 1981, with the objective to study behaviour of the herbicides bentazon and paraquat applied separately or in mixtures in some bean cultivars and in some weeds. Two experiments were conducted in the field. The bean cultivars studied were Carioca and Moruna. The treatments carried on were: bentazon at 0,48 and 0,96 kg/ha; paraquat at 0,05 and 0,10 kg/ha and the tank mixtures with 0,48 + 0,05; 0,96 + 0,10; 0,48 + 0,10 and 0,96 + 0,05 kg/ /ha of bentazon + paraquat respectively. Visual evaluations were performed to quantify the percentage of injury on the bean cultivars, and on the weeds. Colby formula was utilized to evaluate the effects of the mixtures. The results showed that the mixtures induced evident antagonistic effects on the studied cultivars. The treatments carried in the field had no influence on the Carioca and Moruna cultivars yield. On sandy soil and with low precipitation, the synergism of the mixtures was evident on Sida glaziovii K. Sch. and Portulacca oleracea L. In clay soils with normal precipitations, the synergistics effects were evident on Brachiaria plantaginea (Link) Hitch., Eleusine indica (L.) Gaertn., and Alternanthera ficoidea (L.) R. Br.